SIMULATION OF PUBLIC ROADSIDE PARKING TARIFFS AS AN EFFORT TO ELEVATE REGIONAL RETRIBUTION - Rochmat Aldy, Purnomo; Adi, Santoso; Indah Puji, Astuti; Dhutarso Aviantoro, Aviantoro; Aulia Hapsari Juwita, Juwita; Farah, Zaini; Richard, Tomlins (Malaysian Institute of Planners, 2023)
n the PonorogoRegency RPJMD (Local government medium-term development plan) 2016-2021, the vision and policy direction taken by the local government is to increase people's welfare based on religious and cultural values. Regarding regional taxes and regional retribution (PDRD), regional autonomy can be implemented accurately, broadly, responsibly, and independently for government financing, and regional development can be adequately realized through local own-source revenue (PAD). On local own-source revenue, one of thesources of retribution is the public roadside parking tariff. In this case, Ponorogo Regency has a long road, which requires an effective and efficient parking arrangement. This study, therefore, aims to simulate and analyze parking retribution in Ponorogo Regency. The research method used descriptive quantitative and was carried out in several parking zones in Ponorogo Regency. The simulation employed a comparison between fixed, progressive, incidental, and a combination of the three. The simulation results uncovered that weekday retribution includes a fixed tariff at 21.38%, the combined tariff at 32.08%, and the incidental tariff at 46.52% of the total retribution revenues. On weekdays, there was a potential difference between fixed and combined tariffs of 10.69%, and the difference in potential retribution between combined and incidental tariffs was 14.44%. In addition, the parking tariff retribution during incidental activities revealed a fixed tariff of 21.43%, a combined tariff of 32.14%, and an incidental tariff of 46.41% of the total retribution revenues for incidental activities. The difference in potential retribution during incidental activities between fixed and combined tariffs was 10.71% and between combined and incidental tariffs was 14.27%